Contemporary survival and anticoagulation of patients with atrial fibrillation: A community based cohort study in China - Wei, Yong; Zeng, Qingye; Cai, Lidong; Wang, Xingjie; Wang, Bin; Shen, Chaoying; Li, Chao; Wang, Caihong; Shen, Yahong; Yang, Shunhong; Wu, Xiaoyu; Liu, Yan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Backgrounds The understanding of death in patients with atrial fibrillation (AF) in China is limited. This study aimed to assess the contemporary survival of AF patients in China and to explore risk factors for deaths. Methods This was a prospective community-based cohort study including 559 AF patients, who were followed-up from July 2015 to December 2020. Results During 66-month follow-up, there were 200 deaths (56.5% cardiovascular, 40.0% non-cardiovascular, and 3.5% unknown causes) among 559 AF patients with the median age of 76 years. The top three causes of death were heart failure (33.0%), ischemic stroke (17.0%) and cancer (16.5%). Multivariate Cox regression analysis indicated baseline variables positively associated with all-cause death were age (HR: 1.10, 95% CI: 1.08-1.13), AF subtype (HR: 1.37, 95% CI: 1.08-1.73), prior myocardial infarction (HR: 3.40, 95% CI: 1.48-7.78), previous tumor (HR: 2.61, 95% CI: 1.37-4.98), hypoglycemic therapy at baseline (HR: 1.81, 95% CI: 1.13-2.91), but body weight (HR: 0.98, 95% CI: 0.97-1.00) and use of calcium channel blocker (CCB) (HR: 0.62, 95% CI: 0.41-0.95) played a protective role to all-cause death. Of patients who were alive at the end of follow-up, 24.0% were on oral anticoagulants (OAC) alone, 4.5% on dual antithrombotic therapy, 33.1% on antiplatelet agents alone and 38.4% weren’t on any antithrombotic medication. Conclusions Ischemic stroke still remains one of the leading causes of death and OAC is seriously underused in AF patients in China. Independent risk factors for death are age, AF subtype, previous tumor, prior myocardial infarction, hypoglycemic therapy, low body weight and no CCB use.